Smart-RED: A Novel Congestion Control Mechanism for High Throughput and Low Queuing Delay. (4th April 2019) - Bujari, Armir; Marin, Andrea; Palazzi, Claudio E.; Rossi, Sabina
Abstract : We consider the scenario in which several TCP connections share the same access point (AP) and a congestion avoidance/control mechanism is adopted with the aim of assigning the available bandwidth to the clients with a certain fairness. When UDP traffic with real-time requirements is present, the problem becomes even more challenging. Very well-known congestion avoidance mechanisms are the Random Early Detection (RED) and the Explicit Congestion Notification (ECN). More recently, the Smart Access Point with Limited Advertised Window (SAP-LAW) has been proposed. Its main idea is that of computing the maximum TCP rate for each connection at the bottleneck, taking into account the UDP traffic to keep a low queue size combined with a reasonable bandwidth utilization. In this paper, we propose a new congestion control mechanism, namely, Smart-RED, inspired by SAP-LAW heuristic formula. We study its performance by using mean field models and compare the behaviours of ECN/RED, SAP-LAW, and Smart-RED under different scenarios. We show that while Smart-RED maintains some of the desirable properties of the SAP-LAW, it solves the problems it may have in case of bursty UDP traffic or TCP connections with very different needs of bandwidth.